2001
DOI: 10.1046/j.1365-2133.2001.04235.x
|View full text |Cite
|
Sign up to set email alerts
|

A case of Rombo syndrome

Abstract: Rombo syndrome is a rare entity characterized by the presence of atrophoderma vermiculatum of the face, multiple milia, telangiectases, acral erythema and a propensity to develop basal cell carcinomas. We describe a patient whose clinical and histopathological abnormalities are consistent with this diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 5 publications
1
27
0
2
Order By: Relevance
“…True milia cysts were reported histologically in the original description of the syndrome. 69 However, biopsy specimens in a subsequent report showed vellus hair cysts rather than true milia, 71 suggesting heterogeneity in lesions and/or cases described as Rombo syndrome.…”
Section: Rombo Syndrome (Omim 180730)mentioning
confidence: 96%
See 1 more Smart Citation
“…True milia cysts were reported histologically in the original description of the syndrome. 69 However, biopsy specimens in a subsequent report showed vellus hair cysts rather than true milia, 71 suggesting heterogeneity in lesions and/or cases described as Rombo syndrome.…”
Section: Rombo Syndrome (Omim 180730)mentioning
confidence: 96%
“…[69][70][71] In contrast to BCDS, cutaneous findings tend to arise around 7 to 10 years of age. Initial features include photodistributed atrophoderma vermiculatum and cyanotic erythema.…”
Section: Rombo Syndrome (Omim 180730)mentioning
confidence: 99%
“…There are at least two additional familial syndromes, which have varied clinical presentations and predispose individuals to development of BCC, for which the responsible genetic defects remain unknown. They include Rombo syndrome (OMIM 180730) [Michaelsson et al, 1981;van Steensel et al, 2001] and Bazex-Dupre-Christol syndrome (OMIM 301845) [Bazex et al, 1966;Vabres et al, 1995;Kidd et al, 1996], which most likely includes BCC with milia and coarse, sparse hair (OMIM 109390) [Oley et al, 1992;Vabres and de Prost, 1993].…”
Section: Bccmentioning
confidence: 99%
“…Since then, 2 additional cases have been reported. 14,15 Concerning the first of the latter 2, described by Ashinoff et al, 14 the diagnosis of Rombo syndrome was strongly challenged, whereas the second, described by van Steensel et al, 15 was subsequently found to be identical to the one reported in 1981.…”
Section: Hereditary Basal Cell Carcinomasmentioning
confidence: 98%